Standardizing Patient-Derived Organoid Generation Workflow to Avoid Microbial Contamination From Colorectal Cancer Tissues - Marinucci, Mattia; Ercan, Caner; Taha-Mehlitz, Stephanie; Fourie, Lana; Panebianco, Federica; Bianco, Gaia; Gallon, John; Staubli, Sebastian; Soysal, Savas D.; Zettl, Andreas; Rauthe, Stephan; Vosbeck, Jürg; et al. (Frontiers in Oncology, 2022)
The use of patient derived organoids (PDO) as a valuable alternative to in vivo models significantly increased over the last years in cancer research. The ability of PDOs to genetically resemble tumor heterogeneity, makes them a powerful tool for personalized drug screening. Despite the extensive optimization of protocols for the generation of PDOs from colorectal tissue, there is still a lack of standardization of tissue handling prior to processing, leading to microbial contamination of the organoid culture. Here, using a cohort of 16 patients diagnosed with colorectal carcinoma (CRC), we aimed to test the efficacy of phosphate-buffered saline (PBS), penicillin/streptomycin (P/S), and Primocin, alone or in combination, in preventing organoid cultures contamination when used in washing steps prior to tissue processing. Each CRC tissue was divided into 5 tissue pieces, and treated with each different washing solution, or none. After the washing steps, all samples were processed for organoid generation following the same standard protocol. We detected contamination in 62.5% of the non-washed samples, while the use of PBS or P/S-containing PBS reduced the contamination rate to 50% and 25%, respectively. Notably, none of the organoid cultures washed with PBS/ Primocin-containing solution were contaminated. Interestingly, addition of P/S to the washing solution reduced the percentage of living cells compared to Primocin. Taken together, our results demonstrate that, prior to tissue processing, adding Primocin to the tissue washing solution is able to eliminate the risk of microbial contamination in PDO cultures, and that the use of P/S negatively impacts organoids growth. We believe that our easy-to-apply protocol might help increase the success rate of organoid generation from CRC patients.